The map to the millionth of Hispano America. An Inter-American Cooperative Company - Bowman, Isaiah (2021)
In this speech by Isaiah Bowman, we are shown as a recognized classic reference of the North American school of geography and its relationship with Latin America, where Bowman manifests the great importance that maps play in guiding politics and also in the realization of economic activities, since the map is a technical instrument and not a mere attractive illustration, transcending a simple use as a war instrument where information is power, therefore it is key. Bowman performs a characterization analysis on the official cartography of Peru, Chile, Argentina, Bolivia and Brazil, places that he visited thanks to the Yale University expeditions between 1907 and 1913. Bowman in his works that he was not only limited to the physical geography of the central Andes of South America or the Andes of southern Peru, he also collected a lot of information on the oppression and exploitation of the indigenous, the problem of land and latifundio, how Until the date where the traveler was exploited the Indian without any economic retribution, that perhaps is part of his legacy on the study of Peru, because his works were consulted by various Peruvian and Peruvian academics regarding the Andean-Amazon society in the first years of the twentieth century. A special mention is the process of modernization of cartography with the improvement of technical processes in the twentieth century, with it its use and importance in the construction of states and the hegemonic relationship of the United States with Latin America and the Caribbean until the date. Adding the relationship between the country and the scale of the cartography, suggesting the problems that would arise when speaking of a Millionth Map of Hispano America; The interest of the text is based around this project proposed for the Millonth Map of Hispano America, commenting on the efforts, advances and cooperation of different governments and institutions for the elaboration of this project after World War I 1914 - 1918. The Map to the Millionth of Hispano America would be the base of the Great Pan American Atlas, from a vision of the American Geographical Society (AGS in English) and this was agreed at the Second Assembly of the Pan American Institute of Geography and History - PAIGH technical body attached to the OAS, perhaps there is the importance of why the interest was only technical or geopolitical? Or, what is more interesting, the interest of the United States government to map the coastline of the Pacific Ocean of our continent from Tierra del Fuego to Alaska, to safeguard us from future invasions from other continents.